There Would Always Be a Fairy Tale : More Essays on Tolkien. - Flieger, Verlyn (The Kent State University Press, 2017)
Devoted to Tolkien, the teller of tales and co-creator of the myths they brush against, these essays focus on his lifelong interest in and engagement with fairy stories, the special world that he called faërie, a world they both create and inhabit, and with the elements that make that world the special place it is. They cover a range of subjects, from The Hobbit to The Lord of the Rings and their place within the legendarium he called the Silmarillion to shorter works like "The Story of Kullervo" and "Smith of Wootton Major." From the pen of eminent Tolkien scholar Verlyn Flieger, the individual essays in this collection were written over a span of twenty years, each written to fit the parameters of a conference, an anthology, or both. They are revised slightly from their original versions to eliminate repetition and bring them up to date. Grouped loosely by theme, they present an unpatterned mosaic, depicting topics from myth to truth, from social manners to moral behavior, from textual history to the micro particles of Middle-earth. Together these essays present a complete picture of a man as complicated as the books that bear his name--an independent and unorthodox thinker who was both a believer and a doubter able to maintain conflicting ideas in tension, a teller of tales both romantic and bitter, hopeful and pessimistic, in equal parts tragic and comedic. A man whose work does not seek for right or wrong answers so much as a way to accommodate both; a man of antitheses. Scholars of fantasy literature generally and of Tolkien particularly will find much of value in this insightful collection by a seasoned explorer of Tolkien's world of faërie.